INSTITUTIONAL AND TECHNOLOGICAL MECHANISMS FOR INTEGRATING DIGITAL SERVICES INTO THE INFORMATION AND COMMUNICATION SUPPORT SYSTEM FOR LOCAL COMMUNITIES - Stovban, Mykola; Hoi, Nataliia (Public Management and Policy, 2026)
The relevance of this study stems from the fact that the digital transformation of local communities is increasingly moving beyond the implementation of individual e-services and requires the formation of a comprehensive information and communication support system, within which digital services, registries, communication channels, analytics, and feedback tools function as an integrated whole. This issue takes on particular importance in Ukraine, given the uneven level of digital maturity among communities, limited resources, and the need to improve the accessibility, security, and effectiveness of public services. The purpose of this article is to justify the institutional and technological mechanisms for integrating digital services into the information and communication support system of local communities and to develop a conceptual model for their coordinated interaction. Results. The article systematizes contemporary approaches to the digital transformation of local governance and demonstrates that the most productive approach is an integrated one that combines service-oriented, platform-interoperable, human-centered, and communicative-participatory logics. The key institutional prerequisites for the integration of digital services are identified, including regulatory certainty for digital interaction, organizational and coordination capacity, structured data management, staffing and resource support, and mechanisms for trust, security, inclusivity, and monitoring. The main technological components of an integrated community service architecture are identified: single sign-on, digital identification, interoperable data exchange, core registries, process orchestration modules, digital messaging, analytics, cybersecurity, and digital resilience. A conceptual model of the interaction between institutional, technological, and communicative frameworks is proposed. Conclusions. It is demonstrated that the integration of digital services in local communities should be viewed not as a collection of isolated IT solutions, but as a systemic mechanism for modernizing local governance. The effectiveness of such integration is determined by the alignment of institutional rules, technological compatibility, user-centricity, the quality of feedback, and the system’s capacity for adaptive improvement. The proposed approach creates a theoretical and practical foundation for enhancing the accessibility, security, inclusivity, and effectiveness of digital public services in local communities.